Characterization of different courses of atopic dermatitis in adolescent and adult patients - Garmhausen, Dietlind; Hagemann, T.; Bieber, T.; Dimitriou, I.; Fimmers, R.; Diepgen, Thomas L.; Novak, N. (Allergy, 2013)
Background Atopic dermatitis (AD) starts most often during the first years of life and goes into remission in a high proportion of cases during childhood. However, in severe cases, AD persists until adulthood or starts and relapses later in life. So far, studies investigating the natural course of AD during adolescence and adulthood are rare. The aim of our study was to classify different courses of AD and to correlate these with specific risk factors for severe variants of AD. Methods A detailed clinical examination and retrospective evaluation of the history of the disease were performed in a collective of 725 adolescent and adult patients with AD. Laboratory data including total and specific IgE were evaluated. Results Six hundred and seven patients of 725 patients could be classified into course types. Of these 607 patients 85.7% could be classified into five main different course types of all 31 course types recorded. The highest differences in the number of sensitizations, total immunoglobulin E serum levels and predilection of the skin lesions were observed between patients with an early type of onset of AD and a chronic persisting course until adulthood and patients with a late type of onset of AD, that is, after the 20th year of life. Conclusion Our data show that the natural course of AD can be divided into subgroups that display different clinical features. The data support the assumption of a broad heterogeneity of AD in adolescence and adulthood and emphasize the future need for careful stratification of patients with AD.
Gesehen am 26.01.2021